Size dependent egestion of polyester fibres in the Dublin Bay Prawn (Nephrops norvegicus). (July 2022) - Joyce, Haleigh; Nash, Róisín; Kavanagh, Fiona; Power, Thomas; White, Jonathan; Frias, João
Abstract: Microplastics (MPs) are an extensive global contaminant in the marine environment, known to be ingested by marine organisms. The presence of MPs in the commercially important marine decapod crustacean Nephrops norvegicus (Dublin Bay Prawn) has been documented for the North-East Atlantic and the Mediterranean, however, uncertainties remain about retention times of MPs in the gastrointestinal tract (GIT) of this species. This study aims to investigate the retention times of polyester MP fibres of three sizes (3, 5, and 10 mm in length) and to determine whether the egestion of MP fibres is size and time dependent. Results suggest that MP fibres of different lengths are retained for different periods of time, with larger MP fibres being retained for longer periods (e.g., minimum 96 h for 10 mm fibres). The present study also assesses for the first time, the size dependent relationship of MP fibres under controlled conditions for N. norvegicus . Highlights: Retention and egestion times of different length polyester fibres are size-dependent for Nephrops norvegicus. Microplastic fibres of 3 mm in length were excreted within 24 hours. Microplastic fibres of 5 mm in length were retained for a minimum 72 hours. Microplastic fibres of 10 mm in length were retained for a minimum 96 hours. Fibres of 5 and 10 mm were observed in entangled balls of unintroduced fibres, potentially increasing their retention time.